Side-to-side differences in range of motion, muscle strength, and medial elbow laxity in young baseball players with medial elbow injuries - Morifuji, T.; Nakao, H.; Inaba, T.; Kasubuchi, K.; Hashimoto, M.; Kaneko, M. (The Journal of Physical Fitness and Sports Medicine, 2017)
Medial elbow injuries lead to significant performance decrement in baseball. Repetitive throwing alters mechanical physiology. Some of such changes can increase the risk of medial elbow injuries. However, in young baseball players with medial elbow injuries, these changes have not been fully investigated. Thus, the purpose of this study was to investigate the mechanical physiological changes in young baseball players with medial elbow injuries. Side-to-side differences in (1) range of motion (ROM) of shoulder external rotation (ER)/internal rotation (IR), elbow flexion/extension, forearm supination/pronation, trunk rotation, and hip ER/IR; (2) strength of middle trapezius, lower trapezius (LT), and supraspinatus muscles, and shoulder ER/IR; and (3) medial elbow laxity were measured. Side-to-side differences were significant (p < 0.05). ROM of shoulder ER/IR, elbow flexion/extension, forearm pronation, and hip IR on the throwing side were significantly decreased compared to the non-throwing side. Trunk rotation in the direction of the throwing side was significantly decreased compared to the non-throwing side. LT and shoulder IR strength on the throwing side were significantly greater, while shoulder ER strength on the throwing side was significantly weaker than the non-throwing side. Medial elbow joint space of the throwing side was significantly wider than the non-throwing side. In other measurements, no significant differences were observed between the throwing and non-throwing side. According to our findings, young baseball players with medial elbow injuries experience many side-to-side differences in mechanical physiology. The most interesting finding was that younger players with medial elbow injuries displayed decreased shoulder ER ROM, versus an increase reported in many previous studies.